KRITIK TERHADAP KONSEP PEMBANGUNAN EKONOMI “NEOLIBERAL” - B. Kuspradono (KINERJA, 2003)
This article explores neo-liberal economic development concepts on general and criticism on them in the form of alternatives provided. Actually, the concepts themselves have not been openly accepted by the World Bank and the IMF, while since 1990s both international financial institutions have been for several times forcing the application of the concepts in countries that received loan from the institutions. This topic becomes very important since Indonesia has experienced many economic policies which are forcefully driven or demanded by the IMF or the World Bank. Those kind of policies are, for instance, capital liberalization, trade liberalization, privatization, and structural adjustment program. Neo-liberal development concepts are based on liberal economy ideas only, which consist of free market profit and private asset ownership. The concepts have been applied to many developing countries in the form of structural adjustment program package.Keywords: neo-liberal, structural adjustment, liberalization, economic development